The Foundations of Property Rights:: John Locke’s Theory as a Solution to Brazilian Landowning Issue - Souza, João Pedro Berbert de (2016)
The Brazilian landowning issue has always been the scene of many controversies. Considering the history of social instability and legal uncertainty related to rural issues involving small farmers, large landowners and social movements that strive for land, this article presents a brief historical reflection of private property from its beginnings, through some schools of law and coming to the Brazilian legal system. Based on the ideas of John Locke, this research proposes a reflection on problems involving property rights in Brazil and aims to present new ideas for solving conflicts landowners.